2018
DOI: 10.1590/2317-1545v40n178801
|View full text |Cite
|
Sign up to set email alerts
|

The effect of longitudinal distribution and seed depth on grain yield of common bean

Abstract: -The aim of this study was to quantify the longitudinal distribution of plants in the row and seed depth and their effects on hypocotyl length and diameter and on yield components and grain yield of common bean, specifically the cultivar BRSMG Realce in a Latossolo soil in the Cerrado (Brazilian tropical savanna). The data on plant distances in the row were obtained in the field with the aid of a measuring tape in four rows of 2.5 m length. Seed depth was determined by measuring the length of the hypocotyl tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…The time between planting and emergence is longer in seeds planted at greater depths, favoring the intraspecific competition. The combination of uneven seed spacing and planting depth variability may exacerbate the negative effects on grain yield (Silveira et al 2018). Sangoi et al (2012) found that an increase in within-row spatial distribution negatively affects grain yield in maize.…”
Section: Resultsmentioning
confidence: 99%
“…The time between planting and emergence is longer in seeds planted at greater depths, favoring the intraspecific competition. The combination of uneven seed spacing and planting depth variability may exacerbate the negative effects on grain yield (Silveira et al 2018). Sangoi et al (2012) found that an increase in within-row spatial distribution negatively affects grain yield in maize.…”
Section: Resultsmentioning
confidence: 99%
“…Studying beans, Silveira et al [19] observed that very small distance between plants can cause greater competition between them and reduce the yield per plant and per area. In contrast, greater distances between plants may mean reduction in yield per area since more empty spaces were left, giving to the weeds a chance to arise.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the title of this paper, many authors are investigating seed distribution with different types sowing machines [15][16][17][18]. Also, the main problem of sowing is to determine longitudinal, lateral and depth seed distribution [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%